2011
DOI: 10.1152/ajpcell.00429.2010
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxin 1A regulates surface expression of β-cell ATP-sensitive potassium channels

Abstract: The pancreatic ATP-sensitive potassium (K(ATP)) channel consisting of four inwardly rectifying potassium channel 6.2 (Kir6.2) and four sulfonylurea receptor SUR1 subunits plays a key role in insulin secretion by linking glucose metabolism to membrane excitability. Syntaxin 1A (Syn-1A) is a plasma membrane protein important for membrane fusion during exocytosis of insulin granules. Here, we show that Syn-1A and K(ATP) channels endogenously expressed in the insulin-secreting cell INS-1 interact. Upregulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…It was suggested that the lower expression of K ATP channels at the membrane is caused by an accelerated endocytosis and a decreased biogenesis, as well as altered traffic to the membrane of these channels. The authors even proposed that physiologic and pathologic changes in Syn-1A expression may control the K ATP channel expression, thus modulating insulin secretion (Chen et al, 2011).…”
Section: Pharmacology Of K Atp Channels In Pancreatic Beta Cellsmentioning
confidence: 99%
“…It was suggested that the lower expression of K ATP channels at the membrane is caused by an accelerated endocytosis and a decreased biogenesis, as well as altered traffic to the membrane of these channels. The authors even proposed that physiologic and pathologic changes in Syn-1A expression may control the K ATP channel expression, thus modulating insulin secretion (Chen et al, 2011).…”
Section: Pharmacology Of K Atp Channels In Pancreatic Beta Cellsmentioning
confidence: 99%
“…The beads were washed three times with lysis buffer, and proteins were eluted by incubation with SDS sample buffer. Eluted proteins were separated by SDS-PAGE, and SUR1 was detected with an anti-SUR1 antibody as described previously (49).…”
Section: Transduction Of Ins-1 Cells or Human Islets Withmentioning
confidence: 99%
“…K ATP channel activity is suppressed by a SNARE protein, syntaxin 1A, via protein-protein interactions with the SUR subunits [72][73][74][75] . Syntaxin 1A decreases the activity [76] and the membrane expression level of K ATP channels [77] . Syntaxin 1A binding to the SUR1 subunit also attenuates the effect of K + channel openers, such as diazoxide, NNC55-0462, P1075, and cromakalim [78,79] .…”
Section: Introductionmentioning
confidence: 99%